Self-care behavior and self-care agency in lowering salt consumption in hypertensive older patients based on orem's self-care theory - Mina Hosseinzadeh; Nader Mahdavi; Sousan Valizadeh; Marjaneh M Fooladi; Farnaz Rahmani; Farnaz Ghanouni; Parvaneh Aghajari (Social Health and Behavior, 2019)
Introduction: Hypertension is a common chronic disease with multiple systemic complications. Reducing dietary salt intake is one of the most effective and economical methods for managing hypertension. The aim of this study was to investigate self-care agency and self-care behaviors of patients with hypertension in reducing dietary salt and its related factors in Tabriz. Methods: In a cross-sectional study, 250 hypertensive adults were selected in June 2016–2017 from a pool of referred patients to the general clinic at one large teaching hospitals in Iran. They were selected through purposive sampling method. The data collection tools included a demographic questionnaire, self-care agency scale, and self-care behaviors scale. Statistical analysis included simple and multiple (multivariable) linear regression. Results: For dietary sodium reduction, the mean scores (standard deviation) of self-care agency and self-care behaviors were 37.4 ± 10.04 and 36.5 ± 7.8, respectively. Variables with a significant correlation with self-care agency were marital status, age, and the years of hypertension diagnosis (P < 0.001), and for self-care behaviors were marital status and self-care agency (P < 0.001). Conclusion: The findings of this study showed that single and older patients with a recent diagnosis of hypertension had a low score in self-care agency and self-care behavior. Therefore, health-care providers can focus their educational activities on these individuals to enhance their self-care behaviors and agency.